2016
DOI: 10.1074/jbc.m115.680371
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosome Lytic Factor-1 Initiates Oxidation-stimulated Osmotic Lysis of Trypanosoma brucei brucei

Abstract: Human innate immunity against the veterinary pathogenTrypanosoma brucei brucei is conferred by trypanosome lytic factors (TLFs), against which human-infective T. brucei gambiense and T. brucei rhodesiense have evolved resistance. TLF-1 is a subclass of high density lipoprotein particles defined by two primate-specific apolipoproteins: the ion channel-forming toxin ApoL1 (apolipoprotein L1) and the hemoglobin (Hb) scavenger Hpr (haptoglobin-related protein). The role of oxidative stress in the TLF-1 lytic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…That is, does APOL1 directly stimulate autophagic pathways or does APOL1-mediated cell death trigger secondary activation of autophagic pathways? APOL1-dependent cytotoxicity results from ion fluxes after its insertion into the plasma membrane 38, 39 , similar to mechanisms of trypanolysis reported by some but not all investigators 13, 14 . Pore forming toxins of pathogens can activate autophagy in cells 47, 48 suggesting that the observed induction of autophagy by APOL1 expression systems may be a cellular response to APOL1 mediated channel activity.…”
Section: Apol1-activated Signaling Pathwayssupporting
confidence: 77%
See 2 more Smart Citations
“…That is, does APOL1 directly stimulate autophagic pathways or does APOL1-mediated cell death trigger secondary activation of autophagic pathways? APOL1-dependent cytotoxicity results from ion fluxes after its insertion into the plasma membrane 38, 39 , similar to mechanisms of trypanolysis reported by some but not all investigators 13, 14 . Pore forming toxins of pathogens can activate autophagy in cells 47, 48 suggesting that the observed induction of autophagy by APOL1 expression systems may be a cellular response to APOL1 mediated channel activity.…”
Section: Apol1-activated Signaling Pathwayssupporting
confidence: 77%
“…The initial report showed lysosomal membrane targeting resulting in chloride influx 11 . However others demonstrated APOL1 targets the plasma membrane through endosomal recycling and functions as a non-selective, cation channel 13,14,18 . In contrast to data that have demonstrated low pH allows ion fluxes, other investigators have found that APOL1, inserted into membranes in acid environments, remains inactive, only permitting ion flux when exposed to physiological pH 18 .…”
Section: Apol1 and Trypanolysismentioning
confidence: 99%
See 1 more Smart Citation
“…10 Its ability to form channels in lipid bilayers is central to its trypanolytic activity. [11][12][13][14] The APOL1-G2 variant confers enhanced protection from infection with the trypanosomal subspecies, Trypanosoma brucei rhodesiense, and the APOL1-G1 variant is associated with less severe clinical disease after infection with another trypanosomal subspecies, Trypanosoma brucei gambiense. 15 These trypanosomal subspecies cause African sleeping sickness in humans and a single APOL1-G1 or -G2 allele confers these selective advantages, which have likely driven their high frequencies in black populations.…”
mentioning
confidence: 99%
“…26,28,30 Lysosomal damage, a proposed mechanism of trypanolysis, 12 has also been implicated in APOL1-mediated mammalian cytotoxicity. 26 Finally, similar to other trypanolytic mechanisms, [11][12][13][14] APOL1-mediated cell death can result from its channel activity when it inserts into the plasma membrane, which allows loss of cellular ion gradients, osmotic swelling, and ultimately cell death. 28,30 A key question that remains outstanding is whether the APOL1-G1 and -G2 cause differential effects on cytotoxicity compared with APOL1-G0, and whether cytotoxicity is the mechanism driving the pathogenesis of APOL1-associated kidney diseases.…”
mentioning
confidence: 99%